60 GHz broadband variable gain mixer using positive feedback in 65 nm CMOS. Issue 19 (4th September 2015) - Wang, Chong; Li, Zhiqun; Li, Qin; Wang, Zhigong
Abstract : A 60 GHz down‐conversion mixer for a superheterodyne receiver with an IF frequency of about 12 GHz is reported. On the basis of the double‐balanced Gilbert cell, the mixer comprises two series LCR networks to enlarge the IF bandwidth (BW) and a cross‐coupled pair used as positive feedback to the raise conversion gain (CG) at the load stage. By adjusting the bias of the cross‐coupled pair, the mixer features a variable CG. The mixer core only consumes 2.8 mA from a 1.2 V supply when the cross‐coupled pair is turned off, whereas the corresponding a 3 dB IF BW is from 6.5 to 17.5 GHz with a 3 dB CG, which is believed to be the widest IF BW ever reported for a 60 GHz down‐conversion mixer with an IF frequency of about 12 GHz. The CG can be enhanced by driving the cross‐coupled pair, which consumes another 2.4 mA, i.e. 5.2 mA in all for the mixer core. The CG will reach 7.5 dB and the corresponding 3 dB IF BW is from 8 to 16 GHz, where the CG and BW product against power consumption is also believed one of the best results ever reported for a 60 GHz down‐conversion mixer with IF frequency of about 12 GHz.